A Theory of How Workers Keep up with Inflation - Afrouzi, Hassan; Blanco, Andres; Drenik, Andres; Hurst, Erik (Quarterly Journal of Economics, 2026)
We develop a model that integrates modern theories of labor market flows with nominal wage rigidities to study the consequences of inflation on the labor market. Nominal wage stickiness incentivizes workers to engage in job-to-job transitions after an unexpected increase in the price level. Such dynamics lead to a rise in aggregate vacancies associating a seemingly tight labor market with lower real wages—two facts observed during the recent inflation period. The calibrated model jointly matches aggregate and cross-sectional trends in worker flows and wages during the 2021–2024 period. Using historical data, we show that prior periods of high inflation were also associated with increasing vacancies and upward shifts in the Beveridge curve. Our results suggest that policy makers and academics should be cautious about viewing the rise in the vacancy-to-unemployment rate as a sign of a tight labor market during inflationary periods without holistically looking at other labor market indicators.